2006
DOI: 10.4028/www.scientific.net/kem.324-325.599
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Porous Structure and Fatigue Behavior of C/C Composites

Abstract: Porous structure is an important component in C/C composites, which directly affects the fatigue behavior of materials. Therefore, it is necessary to discuss the evolution of porous structure in C/C composites under the fatigue loading. In present work, the character of porous structure in original C/C composites was summarized and the evolution of porous structure after fatigue loading was analyzed. The positive effect of the porous structure evolution after fatigue loading on the reinforcing behavior of fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The results indicated that the critical reaction temperature between W and C was 1200°C. C/C composites were composed of the carbon fiber, pyrolytic carbon matrix with a lamination microstructure, and 4-6 vol.% pores resulting from the preparation method of chemical vapor infiltration [17,18]. In general, the atoms on a void surface diffuse from high chemical potential regions to low chemical potential region, which causes the void to change its shape or drift along the metal line.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the critical reaction temperature between W and C was 1200°C. C/C composites were composed of the carbon fiber, pyrolytic carbon matrix with a lamination microstructure, and 4-6 vol.% pores resulting from the preparation method of chemical vapor infiltration [17,18]. In general, the atoms on a void surface diffuse from high chemical potential regions to low chemical potential region, which causes the void to change its shape or drift along the metal line.…”
Section: Methodsmentioning
confidence: 99%
“…In the rectangular waveguide as shown in Fig. 2, the input impedence in the face of sample away from the short circuit board is L Z , the waveguide is filled with air, which can be regarded as lossless transmission line, meanwhile j γ β = , taking these parameters into the expression (2) can get the load impedence as follows [4]:…”
Section: Samplementioning
confidence: 99%
“…19,20 The laminative pyrolytic carbon was beneficial to the diffusion of W element toward the interior of the C/C composite substrate. Figure 8 shows SEM micrograph and EDS spectrum of the cross section of W-coated C/C composite after heat treatment.…”
Section: Experimental Processmentioning
confidence: 99%